1997
DOI: 10.1007/s002340050387
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of third ventriculostomy patency with phase-contrast MRI velocity measurements

Abstract: Our purpose was to explore the utility of cine phase-contrast MRI velocity measurements in determining the functional status of third ventriculostomies, and to correlate the quantitative velocity data with clinical follow-up. We examined six patients with third ventriculostomies and 12 normal subjects by phase-contrast MRI. The maximum craniocaudal to maximum caudocranial velocity range was measured at regions of interest near the third ventricular floor, and in cerebrospinal fluid anterior to the upper pons a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 13 publications
0
31
0
Order By: Relevance
“…In 2DPC studies, the CSF flow is the result of alternating upward (diastolic) and downward (systolic) motion in each cardiac cycle across the third ventriculostomy site [16]. We performed T2 FSE sagittal MRI sequences and 2DPC studies in our patients to demonstrate the flow.…”
Section: Discussionmentioning
confidence: 99%
“…In 2DPC studies, the CSF flow is the result of alternating upward (diastolic) and downward (systolic) motion in each cardiac cycle across the third ventriculostomy site [16]. We performed T2 FSE sagittal MRI sequences and 2DPC studies in our patients to demonstrate the flow.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] A number of studies worldwide have reported favorable outcomes; 4-6 however, in some cases, ETV fails to resolve symptoms, even when it is technically successful with adequate patent stoma and fenestrated Lillequist membrane. [7][8][9][10][11] It has been hypothesized that patients might suffer from hydrocephalus caused by other obstructive membranes or by fibrosis in the subarachnoid space, especially around basal cisterns. Cine phase-contrast magnetic resonance imaging (PC MR) has been utilized as a method of distinguishing between ABSTRACT: Background: To predict success of endoscopic third ventriculostomy (ETV) in patients with obstructive hydrocephalus, we evaluated pre-and post-operative phase-contrast cine magnetic resonance images (PC MRI) on cerebrospinal fluid (CSF), cine flow in basal cisterns around the brain stem, and cervical medullar junction (CMJ) retrospectively.…”
mentioning
confidence: 99%
“…These features were consistent with the diagnosis of AS. 3 Endoscopic third ventriculostomy was performed to arrest progression of the hydrocephalus. 4 Ventriculographic guidance provided visualization of the distended architecture of the lateral ventricle and vascular structures ( figure 1D).…”
mentioning
confidence: 99%